Helping looked-after children and young people cope when they are ill - Anne Wilson (Scottish Journal of Residential Child Care)
While everyone would wish that all children should be in a state of physical, mental and social wellbeing, this should apply even more to children and young people who are looked after away from home. Unfortunately, research shows that they are among our most disadvantaged young people in terms of their health and wellbeing (Scott and Hill, 2006). There are problems with longer-term preventive care in the form of health surveillance and routine immunisations (Residential Care Health Project, 2004). It should also be recognised that they may face difficulties in the shorter term, when they are ill. Corporate parenting is one way that should ensure that looked-after children who become ill are helped. This paper seeks to explore the views of some of those involved in corporate parenting when a child is ill. It will outline some of the findings of a project by Action for Sick Children (Scotland). This project looked at the healthcare needs and priorities at times of illness for children and young people who are looked after away from home. As part of that work we